Identification of candidate pheromones and neurotransmitter regulation of agonistic behavior in Macrobrachium rosenbergii - Hangyu Qi; Qi Shen; Jiongying Yu; Miaoying Cai; Jianyu Song; Junjie Wu; Guoliang Yang; Shaokui Yi (Aquaculture Reports)
Macrobrachium rosenbergii, a crucial commercial prawn species in China, exhibits agonistic behavior under high-density culture conditions, which negatively impacts their integrity, survival, and growth, causing economic losses. This study utilized liquid chromatography mass spectrometry (LC-MS) to identify and classify the metabolic differences in urine and water mixtures of M. rosenbergii displaying agonistic behavior versus those without. Seventeen compounds, such as 4-Acetamidobutyric acid, 1-oleoyl-2-myristoyl-sn-glycero-3-phosphocholine, N-Acety-L-valine, 11-Dehydrocorticosterone, Sphinganine (Sph t18:0), and Acitretin, were identified as candidate pheromones associated with agonistic behavior, 4-Acetamidobutyric acid and Sph (t18:0) were hypothesized to be particularly significant. Additionally, the roles of serotonin (5-HT) and dopamine (DA) in agonistic behavior among M. rosenbergii males were evaluated. We found that 5-HT levels in hemolymph significantly decreased after fighting (P < 0.05), while DA levels significantly increased (P < 0.05) compared to the control group. The receptor genes of 5-HT and DA (5-HTRs and DARs) were further analyzed. Gene expression analyses of M. rosenbergii before and after agonistic behavior revealed that Mr5-HTR1 exhibited significant changes in hemolymph and abdominal ganglia, while Mr5-HTR2 varied across five tissues, and MrDAR1 and MrDAR2 showed significant changes in the brain and abdominal ganglia. To verify the impact of 5-HTRs on the agonistic behavior, 5-HTRs agonist and antagonist were in vivo injected. The results showed that the injection of 5-HTRs agonists significantly inhibited the occurrence of agonistic behavior in M. rosenbergii. This study deepens our understanding of the regulatory mechanisms of crustacean agonistic behavior and provides a theoretical basis for improving the crustacean farming management.